Abortion rites a social history of abortion in America - Olasky, Marvin N. (Wheaton, IL Crossway, 1992)
Includes bibliographical references and indexes.
Keywords: Abortion -- United States -- history; Pro-life -- United States -- history; Pro-choice -- United States -- history